Changes in blood monocyte functional profile in breast cancer - A. A. Fedorov; E. A. Prostakishina; M. R. Patysheva; A. A. Frolova; P. S. Iamshchikov; I. V. Larionova; M. N. Stakheyeva; M. S. Dorofeeva; O. D. Bragina; E. L. Choynzonov; J. G. Kzhyshkowska; N. V. Cherdyntseva (Сибирский онкологический журнал, 2023)
The purpose of the study was to identify functional features of circulation monocytes in patients with nonmetastatic breast cancer.Material and Methods. The study cohort consisted of 10 breast cancer patients treated at Tomsk Cancer Research Institute. 7 healthy female volunteers were enrolled as a control group. CD14+16-, CD14+16+ and CD14-16+ monocytes subsets were obtained from blood by sorting. Whole transcriptome profling was provided in monocytes from patients and healthy females. Macrophages were differentiated from the obtained monocytes under in vitro conditions. The ability of conditioned media obtained from macrophages to infuence apoptosis and proliferation of MDA-MB 231 cell line was evaluated.Results. Transcriptomic profling revealed signifcant changes in monocytes of breast cancer patients. CD14+16- subset showed higher expression of transporters ABCA1 and ABCG1; chemokines CCR1, CRRL2, CXCR4; maturation and differentiation factors Mafb and Jun; endocytosis mediating factors CD163 and Siglec1; proteases and tetrasponins ADAM9, CD151, CD82, and growth factor HBEGF in patient group. Macrophages derived from monocytes of breast cancer patients produced factors that supported proliferation of the MDA-MB 231 cell line, which was not observed for monocytes from healthy volunteers.Conclusion. Thus, breast carcinoma has a systemic effect on peripheral blood monocytes, programming them to differentiate into macrophages with tumor supporting capacity.